Human papillomavirus vaccines: organisation and experience of preclinical studies - A. S. Korovkin; T. N. Nikitina; T. Yu. Kozlova; D. V. Gorenkov; A. R. Volgin (Биопрепараты: Профилактика, диагностика, лечение)
INTRODUCTION. Vaccination is the main measure for the primary prevention of human papillomavirus (HPV)-related diseases. The development of novel vaccine candidates is underway worldwide, including in the Russian Federation. At the same time, the clinical introduction of new HPV vaccines is seriously hampered by the lack of clear and unambiguous recommendations for conducting preclinical studies of these vaccines.AIM. This study aimed to analyse regulatory documents on HPV vaccines, to study the experience of conducting preclinical studies, and to summarise the preclinical approaches that could be recommended for developers and applicants seeking approval for new preventive HPV vaccines, including the vaccines being developed in the Russian Federation.DISCUSSION. The authors have analysed regulatory documents issued by the World Health Organisation (WHO), the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH), and the Council of the Eurasian Economic Commission (EEC). Additionally, the authors have reviewed the experimental results of preclinical studies of HPV vaccines. The known licensed and pipeline HPV vaccines are similar in terms of their characteristics and constructive features. However, there may be some differences in the HPV serotype coverage and the methods used to produce the HPV L1 capsid protein. To date, studies have confirmed the role of the HPV L1 capsid protein in the development of specific immunity, rendering challenge tests in animal models unnecessary. Papillomatosis modelling may be required for choosing an alternative immunological target or for studying an alternative (non-parenteral) route for vaccine administration. Preclinical study programmes may be supplemented with individual stages of comprehensive assessment of adjuvants and other additives included in novel HPV vaccine compositions.CONCLUSIONS. The authors have studied the international experience and presented a systemic overview of the methods and approaches used in preclinical studies of HPV vaccines. The authors have formulated recommendations for developers for the planning and organisation of preclinical studies of HPV vaccines (including immunogenicity, toxicity, and local tolerance assessments required for licensing new vaccines).